Antiphospholipid antibodies can specifically target placental mitochondria and induce ROS production. Issue 111 (July 2020) - Zussman, Rachel; Xu, Lance Y.; Damani, Tanvi; Groom, Katie M.; Chen, Qi; Seers, Blake; Viall, Chez A.; Chamley, Lawrence W.; Hickey, Anthony
Abstract: Women with antiphospholipid antibodies (aPL) have increased risks of pregnancy complications, including a ten-fold increased risk of preeclampsia, which is potentially triggered by the release of placental toxins. Previously, aPL were shown to enter the outer layer of the placenta, the syncytiotrophoblast, associate with mitochondria, and alter mitochondrial function. We hypothesised that aPL may also increase mitochondrial reactive oxygen species (ROS) production, leading to cellular dysfunction and release of toxins. First trimester placental explants were incubated with monoclonal aPL, ID2 and IIC5 (25, 50, and 100 μg/mL), for 3 h at 37 °C and ROS production followed using CellROX Deep Red. In addition, the candidate treatment compounds chloroquine, melatonin, and Mito-Q were tested at therapeutic concentrations for their ability to prevent ROS production. Mitochondria isolated from term placentae were incubated with fluorescently-labelled ID2, IIC5, or control IgG antibodies (2.5, 5, 10, or 20 μg/mL) for 30 min, and mitochondria with bound antibodies were quantified using flow cytometry. In addition, respirometry coupled with fluorimetry was used to interrogate explant mitochondrial respiration and ROS production following incubation with 25, 50, or 100 μg/mL ID2, IIC5, or control IgG for 3 h at 37 °C. ID2 increased explant ROS production in a manner that was completely prevented by the endocytosis inhibitor chloroquine, and partially prevented by the antioxidants melatonin and Mito-Q. Both ID2 and IIC5 displayed a greater ability to bind isolated mitochondria than control antibodies, and increased ROS production attributable to the mitochondrial enzyme glycerol 3-phosphate dehydrogenase (mGPDH). Our evidence supports the hypothesis that aPL interact with syncytiotrophoblast mitochondria, likely via the binding of cardiolipin and β2 glycoprotein I in mitochondrial membranes, and induce ROS production which contributes to overall oxidative stress and placental dysfunction. Highlights: Antiphospholipid antibodies induce reactive oxygen species by placental explants. Chloroquine abolishes antiphospholipid-induced ROS production by placental explants. β2 GPI is present with isolated placental mitochondria. Antiphospholipid antibodies bind to mitochondria. Some antiphospholipid antibody-induced placental ROS is produced by mitochondria.